ENVIRONMENTAL DEGRADATION AND RISK OF DESERTIFICATION IN ALTO SERTÃO REGION, ALAGOAS STATE, BRAZIL - de Oliveira Santos, João Paulo; da Silva Júnior, José Marcelino; da Silva Filho, José Adalberto; Carneiro da Silva, José Luiz; do Nascimento Ribeiro, José Kennedy; Fernandes de Oliveira, Francisco Ítalo (Revista Geama, 2017)
In this research, the authors evaluated the degree of degradation of the Caatinga biome in Sertão do São Francisco Microregion, Alagoas State, Brazil, by the association of these results with the aridity. We obtained a panorama of the desertification propensity in this area. From the aridity index (IA), the region was classified as having a semi-arid condition (0.2 ? IA <0.5). It was observed values of IA less than 0.50, characterizing an environment with high propensity to establish the state of desertification. From the collected data, we realized the state of degradation of the municipalities in study, all with percentage of anthropic areas greater than 60%. The municipality of Piranhas deserves highlight by the analysis of temporal evolution of the anthropized Caatinga area, with an increase of 44, 661 km² between 2002 and 2009, corresponding to an increase of 17.8% in only seven years. It leads to a scenario where 74.21% of the original Caatinga is in an anthropized state. The critical values of the aridity index, associated to high degree of anthropization may lead to the establishment of desertification process in the study area.